The Scorch trials - Dashner, James, 1972- (New York : Delacorte Press, 2010)
Thomas and the Gladers, having solved the Maze, plan on returning to their lives, but instead find the earth a wasteland with Cranks roaming the desert in search of their next meal and they are faced with the challenge of crossing the Scorch in two weeks in order to arrive at a safe haven.
Sequel to: The maze runner.
School Library Journal, December 2010
Booklist, January 2011
Horn Book, May 2011
Voice of Youth Advocates (V.O.Y.A.), December 2010
Kirkus Review, October 2010
Keywords: Survival -- Juvenile fiction; Science -- Experiments -- Juvenile fiction; Survival -- Fiction; Science -- Experiments -- Fiction; Survival skills -- Fiction; Science -- Experiments -- Fiction; Science fiction; Science fiction